Supporting LGBTIQ+ students in higher education in Australia: Diversity, inclusion and visibility. (October 2018) - Waling, Andrea; Roffee, James A
Objective: Using student narratives of experiences of exclusion and non-inclusion at university, this paper builds an evidence base for, and explores ways in which universities can respond to, the contemporary concerns of lesbian, gay, bisexual, transgender/transsexual, intersex and queer/questioning (LGBTIQ+) undergraduate students. Design: Qualitative exploratory study of undergraduate students who identify as LGBTIQ+ regarding their experiences of exclusion and non-inclusion at university. Setting: Large metropolitan university in Australia. Methods: Sixteen semi-formal interviews with undergraduate students who identify as LGBTIQ+ attending a large Australian university. Data were analysed using phenomenological analysis. Results: Students indicated university-level gaps in service provision and failures to support them in their attempts to access, or create opportunities to access, information regarding sexual and mental health and improve inclusion. They also indicated the importance of queer visibility and its impact in creating a positive experience for LGBTIQ+ members of a campus community. Conclusions: Universities should be aware of the need for formalised diversity and inclusion programmes to tackle contemporary experiences of exclusion. Universities can harness and support student initiatives to better serve the LGBTIQ+ campus community, responding to gaps in knowledge, resources and service needs. These gaps include resources and information regarding sexual health, the provision of gender-neutral toilets and other facilities, and support for peer-led programmes to enhance inclusion. Universities should help increase the visibility of a diverse queer presence on campus to help prevent experiences of exclusion.